2007
DOI: 10.1016/j.devcel.2007.02.019
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Function for the Actin Cytoskeleton in Targeted Exocytosis of Prefusion Vesicles during Myoblast Fusion

Abstract: Myoblast fusion is an essential step during muscle differentiation. Previous studies in Drosophila have revealed a signaling pathway that relays the fusion signal from the plasma membrane to the actin cytoskeleton. However, the function for the actin cytoskeleton in myoblast fusion remains unclear. Here we describe the characterization of solitary (sltr), a component of the myoblast fusion signaling cascade. sltr encodes the Drosophila ortholog of the mammalian WASP-interacting protein. Sltr is recruited to si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
359
3
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 176 publications
(375 citation statements)
references
References 47 publications
10
359
3
3
Order By: Relevance
“…A systematic analysis of these vesicles in wild-type embryos suggests that this complex consists of an average of 1.4 vesicles per complex in an individual section (Estrada et al, 2007). Kim et al (2007) also described variable numbers of vesicles, which were also not all paired, a finding that is supported by Doberstein et al (1997). These observations raise two key questions: (1) Why are the vesicle numbers so different?…”
Section: The Prefusion Complexmentioning
confidence: 87%
See 4 more Smart Citations
“…A systematic analysis of these vesicles in wild-type embryos suggests that this complex consists of an average of 1.4 vesicles per complex in an individual section (Estrada et al, 2007). Kim et al (2007) also described variable numbers of vesicles, which were also not all paired, a finding that is supported by Doberstein et al (1997). These observations raise two key questions: (1) Why are the vesicle numbers so different?…”
Section: The Prefusion Complexmentioning
confidence: 87%
“…Doberstein et al (1997) suggested that these vesicles form a prefusion complex that can consist of up to 15 vesicles (40 nm in diameter) per contact site. From the Golgi to the membrane, they might be transported by F-actin, which disintegrates after prefusion complex formation (Kim et al, 2007). A systematic analysis of these vesicles in wild-type embryos suggests that this complex consists of an average of 1.4 vesicles per complex in an individual section (Estrada et al, 2007).…”
Section: The Prefusion Complexmentioning
confidence: 99%
See 3 more Smart Citations